How to use imaginary cases in normative theory. (29th April 2022) - Dowding, Keith
Abstract : This paper defends the use of imaginary cases in normative theorizing. Imaginary cases are used as a part of an argument and should be assessed in terms of the role they play within arguments. The paper identifies five ways in which they are used and then uses some of the best examples to bring out how they contribute to debates. While not directly akin to empirical experiments, criticisms of imaginary cases can be represented in terms of the well‐known distinction between internal and external validity in social science experiments. While imaginary cases can suffer from internal and external validity problems, these do not constitute a decisive critique of their use as a method of analysis. Criticisms of imaginary cases should detail the precise form in which they are used, and why any particular use is invalid, internally or externally, in the context of the argument for which the case is presented.